The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1007/bf03350112
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in patients with Pendred’s syndrome

Abstract: Thyroid function was studied in 17 unrelated patients with Pendred's syndrome. Fourteen patients had been treated with L-thyroxine, which was withdrawn during the investigation. Eight of the patients had previously had a thyroid resection. Thirteen patients had goiter at the time of study. The serum total thyroxine and serum total triiodothyronine concentrations were normal in 8, of whom 3 had elevated serum TSH concentrations. In the remaining 9 cases the thyroxine levels were below normal with elevated TSH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…However, the occurrence of Graves' hyperthyroidism in patients with PS has been reported (Ibrahim et al, 2009). In addition, the familial concurrence of PS and AITD, and the anti-TSHR aAb detection in PS sera has been described (Vaidya et al, 1999;Friis et al, 1988). Thus, PDS could be a common genetic component for the two pathologies (AITD and PS) explaining, therefore, this clinical overlapping signs on the thyroid affection.…”
Section: Discussionmentioning
confidence: 91%
“…However, the occurrence of Graves' hyperthyroidism in patients with PS has been reported (Ibrahim et al, 2009). In addition, the familial concurrence of PS and AITD, and the anti-TSHR aAb detection in PS sera has been described (Vaidya et al, 1999;Friis et al, 1988). Thus, PDS could be a common genetic component for the two pathologies (AITD and PS) explaining, therefore, this clinical overlapping signs on the thyroid affection.…”
Section: Discussionmentioning
confidence: 91%
“…Increased serum thyroglobulin has been reported in Pendred syndrome (5,23). This might mirror the activity of the thyroid gland in terms of hormone production.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, two patients (II-1 in family 1; II-5 in family 2) had overt hypothyroidism. The absence of thyroid antibodies in individual II-1 of family 1 suggests that the hypothyroidism was caused by the organification defect itself, and not by concomitant autoimmune thyroid disease, a recognized confounding entity in patients with Pendred's syndrome (23,24). Autoimmune thyroid disease could not be excluded in individual II-5 of family 2.…”
Section: Discussionmentioning
confidence: 95%
“…The affected patients of family 1 and patient II-5 of family 2 were hypothyroid. Given the absence of antibodies against thyroperoxidase and thyroglobulin, it seems unlikely that the patient of family 1 had concomitant autoimmune thyroid disease, a combination that has been reported in other patients with Pendred's syndrome (23,24). Autoantibodies could not be measured in the hypothyroid patient of family 2, and therefore it is Haplotype analysis revealed that the index patient II-4 is homozygous for microsatellite markers flanking the PDS locus.…”
Section: Clinical and Radiological Findingsmentioning
confidence: 90%